2000
DOI: 10.1089/neu.2000.17.261
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Reduces Metabolic Uncoupling Following Experimental Head Injury

Abstract: Previous investigations have shown that ethanol is neuroprotective following experimental traumatic brain injury (TBI). This study sought to determine if the neuroprotective effects of ethanol in a controlled cortical impact (CCI) injury model are related to its effects on cerebral glucose metabolism and blood flow. Adult rats were given ethanol (1.0 g/kg) or saline by intraperitoneal injection followed 40 min later by injury. Regional cerebral blood flow (CBF) and cerebral metabolic rates of glucose (CMRglc) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(53 citation statements)
references
References 71 publications
1
52
0
Order By: Relevance
“…We believe that this could be because of the use of ethanol as a vehicle, because ethanol has been shown previously to have neuroprotective properties. 28,29 Our study effectively delivered a total of 0.1 g/kg of ethanol to the mice over two administrations. Previous studies have shown that 1 g/kg of ethanol can improve cerebral blood flow and reduce metabolic uncoupling after CCI in mice, 29 and 1.5 g/kg can reduce lesion volume and improve outcome in an ischemia model.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this could be because of the use of ethanol as a vehicle, because ethanol has been shown previously to have neuroprotective properties. 28,29 Our study effectively delivered a total of 0.1 g/kg of ethanol to the mice over two administrations. Previous studies have shown that 1 g/kg of ethanol can improve cerebral blood flow and reduce metabolic uncoupling after CCI in mice, 29 and 1.5 g/kg can reduce lesion volume and improve outcome in an ischemia model.…”
Section: Discussionmentioning
confidence: 99%
“…have suggested that alcohol might have a neuroprotective effect on the brain following traumatic brain injury (TBI) through such mechanisms as inhibiting N-methyl-Daspartate (NMDA) receptor-mediated excitotoxicity (Cebere and Liljequist, 2003;Chandler et al, 1993;Is et al, 2005;Türeci et al, 2004), decreasing the degree of uncoupling between glucose metabolism and cerebral blood fl ow (Kelly et al, 2000), inhibiting the production of pro-infl ammatory cytokines (Gottesfeld et al, 2002), attenuating TBI-induced hyperthermia (Taylor et al, 2002), and blunting the sympathoadrenal response in TBI (Opreanu et al, 2010). Premised on the evidence from animal research, one recent study confi rmed that patients who were intoxicated at the time of injury had better acute neuropsychological outcomes when recovering from TBI than did nonintoxicated patients (Lange et al, 2008).…”
Section: S Everal Animal and Laboratory Studiesmentioning
confidence: 99%
“…The previously characterized CCI injury device (Sutton et al, 1993;Lindner et al, 1998;Kelly et al, 2000) was used to generate a cortical contusion to the left hemisphere. Each animal was placed under inhalation anesthesia with isoflurane (4% for induction, 2.0% for maintenance, in 100% O 2 at 1.5 l/min).…”
Section: Injurymentioning
confidence: 99%